2020
DOI: 10.1002/aelm.201901320
|View full text |Cite
|
Sign up to set email alerts
|

From Unipolar, WORM‐Type to Ambipolar, Bistable Organic Electret Memory Device by Controlling Minority Lateral Transport

Abstract: Write‐once‐read‐many (WORM) memory behavior is often observed in polymer electret memory (PEM) devices, greatly limiting their overall performance. This paper systematically investigates the device physics of PEM devices with poly(α‐methylstyrene) as a charge trapping layer and pentacene as a semiconductor channel. The combined experiments on transistors, capacitances, and optical spectroscopy reveal that both the WORM memory behavior after negative and positive pulses and the gradual formation of memory after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The bistable memory behavior can be related to its ambipolar charge trapping capability, which is favorable for multi-bit data storage application. [27,28] PPyMA prepared from conventional free radical polymerization was also applied to form supramolecular electret with TCNQ, and the resultant memory characteristics were presented in Figure S8, Supporting Information. As seen, PPyMA with a higher (14 170 g mol −1 ) or lower (5620 g mol −1 ) molecular weight contributes similarly to the charge trapping with UV light programming.…”
Section: Performance Of Photonic Fet Memory-employing Ct-based Supram...mentioning
confidence: 99%
“…The bistable memory behavior can be related to its ambipolar charge trapping capability, which is favorable for multi-bit data storage application. [27,28] PPyMA prepared from conventional free radical polymerization was also applied to form supramolecular electret with TCNQ, and the resultant memory characteristics were presented in Figure S8, Supporting Information. As seen, PPyMA with a higher (14 170 g mol −1 ) or lower (5620 g mol −1 ) molecular weight contributes similarly to the charge trapping with UV light programming.…”
Section: Performance Of Photonic Fet Memory-employing Ct-based Supram...mentioning
confidence: 99%
“…Injecting holes or electrons into insulator polymers to tune the threshold voltage of transistors is a general approach for memory applications. [53,58,[65][66][67] However, for unipolar transistors, usually only one type of charges (holes or electrons) could be efficiently injected into and trapped in the electret, so that usually the transfer curves can only be unidirectionally shifted. Therefore, it is difficult to erase the programmed states by the opposite voltage, unless other stimulus (e.g., light or heat) are applied.…”
Section: Reconfigurable Ambipolar Transistors For Multi-level Non-vol...mentioning
confidence: 99%
“…Therefore, it is difficult to erase the programmed states by the opposite voltage, unless other stimulus (e.g., light or heat) are applied. [53,58,63,[67][68][69][70][71] In ambipolar transistors, both holes and electrons could be reversibly trapped and released, which is favorable for reversibly switch the device states for realizing flash-type memories. [9] However, uniformly trapped holes or electrons along the channel just shift the transfer curves to negative or positive voltages, and the remained high off-state current lead to low memory ratios.…”
Section: Reconfigurable Ambipolar Transistors For Multi-level Non-vol...mentioning
confidence: 99%
“…47 Subsequently, the application of electrets in OFET memory has developed rapidly. [48][49][50] Charges trapped in polymer electrets can be generated by the following mechanisms: (i) charges trapped by structural defects and impurity centers; (ii) orientation of dipoles (in polar materials); and (iii) build-up of charges near heterogeneities such as grain boundaries (in polycrystalline materials) and amorphous-crystalline interfaces (in semicrystalline polymers). 51 In 2008, Kim and co-workers systematically studied the characteristics of various polymer electrets, 51 and concluded that only non-polar and hydrophobic polymers could be used as effective dielectrics, acting like floating gates in floating gate memories.…”
Section: Polymer Electret Ofet Memorymentioning
confidence: 99%